Effects of Straw Biochar on Heavy Metal Cu in Soil Under Different Conditions. Issue 2 (19th January 2023) - Guo, Yiping; Tao, Xiangkai; Zhu, Weiyong; Ji, Yapeng; Surendra, K. C.; Khanal, Samir Kumar; Liu, Bingtao; Li, Guoting
ABSTRACT: Biochar has been widely deemed as a soil conditioner to modify the physicochemical and biological properties of soil. In this research, the influence of different biochar application conditions on the effect of heavy metal Cu in soil was detected. In batch experiments, the combinations could definitely enhance the adsorption abilities, and under the combination ratio of 4 wt % biochar, 3 wt % wheat straw, and 5 wt % cow manure compost in the soil, the adsorption rate would be more than 97% in 60 mins. The adsorption kinetics showed the adsorption processes were multiphase diffusion processes and the conversion of activation energy in soil surface was obvious, while the isotherms analysis suggested the adsorption of Cu by the soil under various amendments was mainly monolayer adsorption as well as some other complex reactions. However, in the eluviation experiments, more and more Cu was lost in the leaching solutions when wheat straw and compost were added into the soil as well as biochar. pH values changes indicated that the connections among Cu and solids may be mostly related to the precipitation reaction in the eluviation experiments. FTIR analysis implied that the addition of wheat straw and compost in the biochar could indeed enhance the reaction between heavy metal Cu and soil, however, the reactions were rather complicated, and under the eluviation condition, there was not enough time to form the stable bonds, so more Cu was dissolved into the leaching water.